Second-Person Engagement, Self-Alienation, and Group-Identification - Zahavi, D (Springer Verlag, 2016)
One of the central questions within contemporary debates about collective intentionality concerns the notion and status of the we. The question, however, is by no means new. At the beginning of the last century, it was already intensively discussed in phenomenology. Whereas Heidegger argued that a focus on empathy is detrimental to a proper understanding of the we, and that the latter is more fundamental than any dyadic interaction, other phenomenologists, such as Stein, Walther and Husserl, insisted on the importance of empathy for proper we-experiences. In this paper, I will present some of the key moves in this debate and then discuss and assess Husserl’s specific proposal, according to which reciprocal empathy, second-person engagement and self-alienation are all important presuppositions for group-identification and we-identity.